HUMANIZATION AND HUMANITATION OF MATHEMATICAL EDUCATION AND ROLE OF MATHEMATICAL LOGIC IN THESE PROCESSES - Sinko Ю.І. (Journal of Information Technologies in Education (ITE), 2011)
In this article the speech goes about humanization and humanitation of education in general and mathematical education in particular. Maintenance of these concepts is opened up, the phenomena and processes which they entailed and the role of mathematical logic comes to light in them are examined. Basic directions of development of humanization and humanitation of mathematical education in the modern conditions of educational process of higher school are determined